2010
DOI: 10.1039/b914570b
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of oxygenreduction mechanism at Pt4cluster

Abstract: We used density functional theory to investigate the reaction pathway of oxygen reduction/water splitting at a tetrahedral Pt(4) cluster. Four extra water molecules were included to account for the effect of water in mediating elementary surface processes. We propose a 6-step reaction sequence that includes a proton transfer between neighbouring active sites. Thermochemical considerations and the nudged elastic band method were employed to calculate reaction and activation energies for the elementary reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 42 publications
1
42
0
1
Order By: Relevance
“…Δ G pH and Δ G U are the free energy contributions due to variations in H + concentration and electrode potential, U , respectively. In this work, we consider the contributions of Δ E , Δ G pH and Δ G U to free energy and neglect the effects of other terms60. Effects of other terms will be included in a forthcoming publication.…”
Section: Methodsmentioning
confidence: 99%
“…Δ G pH and Δ G U are the free energy contributions due to variations in H + concentration and electrode potential, U , respectively. In this work, we consider the contributions of Δ E , Δ G pH and Δ G U to free energy and neglect the effects of other terms60. Effects of other terms will be included in a forthcoming publication.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular level studies have revealed that reaction steps involving formation and further reaction of chemisorbed -O and -OH on the Pt surface, including coupled electron-and proton-transfer processes, constitute the energetically most inhibited steps of the ORR mechanism. [52][53][54] The adsorption Gibbs energy of chemisorbed -O and -OH is widely considered as a yardstick in evaluating the electrocatalytic ORR activity of supported or unsupported transition metal catalysts. 55 On the one hand, chemisorbed oxygen species are intermediates of the ORR which should be formed at a high rate; on the other hand, maintaining steady high rates of ORR hinges on sufficient Pt surface sites that are free of chemisorbed oxygen species, a requirement that becomes critical if oxide species are bound too strongly.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 The ultrasmall size of noble-metal clusters is essential for high reactivity. 27 However, NPs of 2−3 nm diameters containing 200 to 500 atoms are beyond the computational capabilities of density functional theory (DFT).…”
Section: ■ Introductionmentioning
confidence: 99%